Characteristics of Fractures among International Travellers in Bali - Ketut Ngurah Bagaskara M; Sri Ratna Dewi (Publication Department, Universitas Warmadewa, 2025)
An increase in the number of foreign tourists in Bali will likely lead to a rise in musculoskeletal traumas, particularly fractures. The characteristics of fractures vary in terms of aetiology, age, and location, as well as the mechanism of injury (MOI), which, in turn, have different forms of treatment. This study aimed to determine fracture characteristics based on demographics, the affected bone fractures, the relationship between the bone and surrounding tissue, and fracture configuration. The research method used is a descriptive observational approach, drawing from patient notes or medical records of patients undergoing inpatient or outpatient treatment between January 2022 and December 2023. The sampling technique used in this research is consecutive sampling. The minimum number of samples required for this research is 96. The data in this research were analysed descriptively and presented in the form of narratives, tables, graphs, or images. The research results showed that respondents who experienced fractures were primarily Russian citizens, accounting for 25% of the total. Most respondents experienced closed fractures, totalling 90. The most common fault lines were complete fractures, with 92 respondents, and experienced transverse fracture characteristics, with 55 respondents. The highest number of fractures occurred in the Metatarsal V, with 20 respondents experiencing single-site fractures.